Alternating therapeutic plasma exchange (TPE) with double plasma molecular adsorption system (DPMAS) for the treatment of fulminant hepatic failure (FHF). Issue 12 (13th December 2021) - Lei, Yan; Liang, Yuling; Zhang, Xuemei; Wang, Xiaohua; Zhang, Yu; Chan, Yuk Ming; Tang, Chun; Zheng, Zhihua
Abstract: Alternating therapeutic plasma exchange with double plasma molecular adsorption system can rapidly remove bilirubin and ammonia and supplement the essential substance from the blood, which could be used as an effective treatment for fulminant hepatic failure. Abstract : Alternating TPE with DPMAS could remove bilirubin and ammonia, which may partially replace liver function and provide transition time for FHF patients waiting for liver transplantation.